1992
DOI: 10.1182/blood.v80.7.1639.bloodjournal8071639
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding the pathogenesis of the anemia of chronic disease [see comments]

Abstract: Improved understanding of the inflammatory response and the identification and characterization of the specific cytokines involved, as well as improved understanding of erythropoiesis, and the availability of recombinant human growth factors such as EPO, have greatly enhanced our appreciation of the pathogenesis of ACD by allowing development of a number of informative models for studying this syndrome. It appears that a variety of cytokines are involved in all aspects of the pathogenesis of ACD, from the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0
22

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(134 citation statements)
references
References 63 publications
0
112
0
22
Order By: Relevance
“…In our study, we also found that the platelet engraftment was poorer for patients with HCT‐CI scores of ≥3 ( P = 0.033). We speculate that this might be the result of direct damage of comorbidities on the marrow microenvironment , or that it might result from increases in a negative regulator of hematopoiesis, such as TNF‐α and IL‐6 . Therefore, a high comorbidity burden may well affect the platelet engraftment negatively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also found that the platelet engraftment was poorer for patients with HCT‐CI scores of ≥3 ( P = 0.033). We speculate that this might be the result of direct damage of comorbidities on the marrow microenvironment , or that it might result from increases in a negative regulator of hematopoiesis, such as TNF‐α and IL‐6 . Therefore, a high comorbidity burden may well affect the platelet engraftment negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of EPO that are inappropriately low for the degree of anaemia have been demonstrated in patients with acquired immunodeficiency syndrome (AIDS), rheumatoid arthritis and other chronic inflammatory diseases, as well as in cancer 136–138 . The blunted EPO response can be mimicked in animals with acute activation of the immune system, 30 as well as in rat isolated perfused kidneys and the human hepatoma cell lines 139 .…”
Section: Dysregulated Expression Of Epo In Different Clinical Statesmentioning
confidence: 99%
“…Anemia of chronic disease (ACD) is well‐observed in chronic inflammatory diseases such as rheumatoid arthritis, malignant neoplasm and so on. The mechanisms of ACD are proposed as disturbances of iron metabolism, reduced erythropoiesis in bone marrow and life span‐shortening of red blood cells (16). Biological contaminations of dialysate lead chronic inflammatory responses in hemodialysis patients, and then lead ACD expressed as erythoropoietin resistance.…”
Section: Clinical Usefulness Of Ultrapure Dialysatementioning
confidence: 99%